Impact of P fertilizer and arbuscular mycorrhizal fungi on forage legume growth, chlorophyll content and productivity - Sanele Mpongwana; Alen Manyevere; Conference Thando Mpendulo; Johnfisher Mupangwa; Wandile Mashece; Mthunzi Mndela (PeerJ, 2025)
Soil phosphorous (P) is the most limiting plant nutrient globally, reducing forage plant productivity. Although inorganic P fertilizers are used, about 75–90% of P becomes unavailable for plant uptake, hence, the strategies to enhance P uptake acquisition, such as the use of arbuscular mycorrhizal fungi (AMF) inoculation, are crucial. A greenhouse pot experiment was conducted under controlled environmental conditions at the University of Fort Hare, where three legume species (Vigna unguiculata, Lablab purpereus and Mucuna pruriens) were grown for 90 days under five P fertilizer levels (0; 0.68; 1.36; 2.04 and 2.72 g P/pot) with or without AMF-inoculation, resulting in 30 treatment factorial arrangement, each replicated 4 times. Agronomic responses to P fertilization and AMF-inoculation were assessed. Plant height, stem diameter, chlorophyll content, and leaf and stem yield were significantly influenced (p < 0.001) by the interaction of phosphorus (P) fertilizer levels, arbuscular mycorrhizal fungi (AMF) inoculation, and legume species. Inoculated plants showed remarkable growth, reaching heights of 94.2 to 159.0 cm compared to 61.1 to 117.0 cm in uninoculated plants. Additionally, inoculated plants had stem diameters twice as large as those of uninoculated plants when grown with 1.36 g P/pot, outperforming other P fertilizer levels by day 90 across all legume species. Likewise, chlorophyll content of inoculated plants (78.1–90.7 soil plant analysis development (SPAD)) was significantly higher than uninoculated plants (56.9–69.1 SPAD) at 1.63 P g/pot compared to 0, 0.68, 2.04 and 2.72 g P/pot. Moreover, inoculated plants attained relatively higher leaf (123.3–144.0 g/pot) and stem yield (75.2–121.8 g/pot) than uninoculated plants at 1.36 g P/pot compared to 0, 0.68, 2.04 and 2.72 g P/pot. Overall, AMF-inoculation improved growth and productivity of forage legumes, but its effects depended on the P fertilizer level, with 1.36 g P/pot being the potential optimum fertilizer rate for soil nutrition of legume pastures.